Doctors' functional leadership in psychiatric healthcare teams – a reversible leadership logic. Issue 3 (8th June 2015) - Berlin, Johan M.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper was to study how psychiatric doctors practise leadership in multidisciplinary healthcare teams. The paper seeks to answer the question: How do psychiatric doctors lead multidisciplinary teams during treatment conferences? Design/methodology/approach – Six psychiatric teams were studied at a university hospital. Each team was observed over a period of 18 months, and data were collected during four years (2008-2011). Data were collected through interviews with doctors (n = 19) and observations (n = 30) of doctors' work in multidisciplinary psychiatric teams. Findings – Doctors in a multidisciplinary team use either self-imposed or involuntary leadership style. Oscillating between these two extremes was a strategy for handling the internal tensions of the team. Research limitations/implications – The study was a case study, performed during treatment conferences at psychiatric wards in a university hospital. This limitation means that there is cause for some caution in generalising the results. Practical implications – The results are useful for understanding leadership in multidisciplinary medical teams. By understanding the reversible logic of leadership, cooperation and knowledge sharing can be gained, which means that a situation of mere peaceful coexistence can be avoided. Understanding the importance of the informal contract makes it possible to switch leadership among team members. A reversible leadership with an informal contract makes the team less vulnerable. The team's professionals can thus easily handle difficult situations and internal tensions, facilitating leadership and management of multidisciplinary teams. Originality/value – Doctors in multidisciplinary psychiatric teams use reversible leadership logic.